HUBUNGAN PEMANFAATAN PERPUSTAKAAN DENGAN HASIL BELAJAR MAHASISWA DIII KEBIDANAN TINGKAT I SEMESTER I DI UNIVERSITAS BATAM TAHUN 2017 - Irawati, Irawati; Mariyana, Mariyana (Universitas Batam, 2017)
The library functions as the facility to support students in learning process by advancing all of the facilities provided, for instance books, journals, e-book, e-journals, and other information sources, for the students learning importance. The purpose of this study is to examine the correlation of library support and the learning outcomes of first-degree midwifery students at the Batam University. This research is an analytic survey research with cross sectional approach which investigates the correlation between risk factors and its effects through an approach, observation, or data collection at one time. This study was conducted from May to July 2017 by distributing the questionnaires to 24 respondents. The data collected from the questionnaires then was analyzed by Chi Square statistical test. Further, the Chi Square statistical test obtains score of p=0.011 (<0.05). Therefore, it is verified that there is a significant correlation of the library support and the first-year students learning outcomes of Diploma III Midwifery study program in Batam University.Â